Enhancing Market Reach: Assessing the Impact of Instagram's Online Promotion Strategy on DOTS Greentea MSMEs in Karawang, Indonesia - Dini Nur Hayati; Puji Isyanto; Neni Sumarni (Jurnal Ekonomi, 2024)
Dots Greentea has experienced fluctuations in revenue due to the COVID-19 virus, intensified competition, and shortcomings in promotional efforts and product innovation. The objective of this research is to assess the effectiveness of online promotion through Instagram in promoting Dots Greentea MSMEs in the city of Karawang. This study adopts a qualitative research approach utilizing observational data, in-depth interviews, and documentation as primary data sources. The primary data, obtained from observations and interviews with relevant stakeholders, encompass questions concerning the activities and events related to Dots Greentea promotion in Karawang. The findings indicate that online promotion significantly influences the increase in Dots Greentea sales. When this business promotes through Instagram, the revenue or income of Dots Greentea increases from 20% to 40%.